Economic Analysis of International Law Contributions to the XIIIth Travemünde Symposium on the Economic Analysis of Law (March 29-31, 2012) - Eger, Thomas; Voigt, Stefan; Oeter, Stefan (Mohr Siebeck, 2014)
The topics covered in this volume range from classics of the on-going discussion on the economic analysis of international law - such as the issue of legitimacy of customary international law - to more recent topics such as internet privacy, private military contractors, the fight against piracy, the International Criminal Court and the highly topical issue of land grabbing.